Quality Assurance for Clinical Trials - Ibbott, Geoffrey S.; Haworth, Annette; Followill, David S. (Frontiers in Oncology, 2013)
Cooperative groups, of which the Radiation Therapy Oncology Group (RTOG) is one example, conduct national clinical trials that often involve the use of radiation therapy. In preparation for such a trial, the cooperative group prepares a protocol to define the goals of the trial, the rationale for its design, and the details of the treatment procedure to be followed. The Radiological Physics Center (RPC) is one of several QA offices that is is charged with assuring that participating institutions deliver doses that are clinically consistent and comparable. The RPC does this by conducting a variety of independent audits and credentialing processes. The RPC has compiled data showing that credentialing can help institutions comply with the requirements of a cooperative group clinical protocol. Phantom irradiations have been demonstrated to exercise an institution’s procedures for planning and delivering advanced external beam techniques (Ibbott et al. 2008, Molineu et al. 2005, Molineu et al. 2013). Similarly, RPC data indicate that a rapid review of patient treatment records or planning procedures can improve compliance with clinical trials (Ibbott et al. 2007). The experiences of the RPC are presented as examples of the contributions that a national clinical trials QA center can make to cooperative group trials. These experiences illustrate the critical need for comprehensive QA to assure that clinical trials are successful and cost-effective. The Radiological Physics Center is supported by grants CA 10953 and CA 81647 from the National Cancer Institute, NIH, DHHS.